دور مواقع التواصل الاجتماعي الفيس بوك في التوعية بمخاطر حوادث المرور والتقليل منها - حميني عبدالمالك; د/بن عزوزي محمد (جامعة عمار ثليجي الاغواط, 2023)
الملخص : تشكل حوادث ابؼ ركر احد أىم الأخطار التي تواجو الإنساف في العصر ابغديث كالتي غدت تستنزؼ المجتمعات بشريا )آلاؼ الوفيات كابعرحى كابؼعاقتُ( كاقتصاديا، كأما ىذه الوضعية ابؼأساكية ظهرت فواعل أخرل إلذ جانب ابؼؤسسات الاجتماعية كأجهزة الأمن، كابؼتمثلة في شبكات التواصل الاجتماعي كالفايسبوؾ كتويتً كاليوتيوب.. الخ حيث تلعب ىذه الأختَة دكرا ىاما في عملية نشر ابؼعلومات كالأخبار ابؼتعلقة بحوادث الستَ . فشبكات التواصل الاجتماعي اليو أضحت تشكل آلية لبناء اتصاؿ فعاؿ في المجتمع في بؾاؿ نشر ثقافة السلبمة ابؼركرية كذلك من خلبؿ توضيح الصور التي تبتُ بـاطر حوادث ابؼركر ككذا نشر مقاطع الفيديوىات ابؼتضمنة النتائج ابؼتًتبة عنها كالتوصيات ابؼتعلقة بالوقاية منها كالقيا كذلك بحملبت توعوية الكتًكنية بزلق لدل الشباب الوعي بدخاطر ابؼركر كتبيتُ ما عليو القيا بو لتجنب مثل ىذه ابغوادث . Abstract : Traffic accidents constitute one of the most important dangers facing man in the modern era, which is depleting Societies, both humanly (thousands of deaths, wounded and handicapped) and economically, and in front of this tragic situation appeared Other actors, in addition to social institutions and security services, represented in social networks Such as Facebook, Twitter, YouTube, etc., as the latter plays an important role in the process of disseminating information and news related to traffic accidents. Today, social networks have become a mechanism for building effective communication in the community in the field of spreading the culture of traffic safety, by clarifying images that show the dangers of traffic accidents, as well as publishing video clips containing the consequences of them and recommendations related to their prevention, as well as carrying out electronic awareness campaigns that create awareness among young people of the dangers. Traffic and explain what he has to do to avoid such accidents.